Nasihat Kyai Zaini Jambi Meliputi Ruang Dan Waktu Sepanjang Zaman (Fid-Dãraini) - Abdul muthalib; Khairuddin Khairuddin (Jurnal Edukasi, 2023)
This letter is addressed to one of the Kyai Pondok Sa'adatasdaraian Jambi, who has a high commitment to preparing his centrinna, who will walk life safely and safely both for now and in the future, even far from that, the Fid-Daraini (dunia-akhirat). Kyai's advice was so bold that he passed it on to his sister-in-law. With that in mind, we'd like to know more about it. This method of research is based on the historical method, the theory of qualitative theory, while the aim is to know further why Kyai Zaini so seriously conveyed it to his sister and to really pay attention to the "advice" consisting of that rule. Though the advice of Kyai Kharismatik Jambi has passed decades ago, if observed deeply, it can be drawn the red thread that wherever a human being lives on this earth, if he follows all the "rules," whether religious rules, rules of state, or customary rules somewhere, then he will live safely and safely, and a healthy life is the dream of everyone.